Exogenous S1P Exposure Potentiates Ischemic Stroke Damage That Is Reduced Possibly by Inhibiting S1P Receptor Signaling - Eunjung Moon; Jeong Eun Han; Sejin Jeon; Jong Hoon Ryu; Ji Woong Choi; Jerold Chun (Hindawi Limited, 2015)
Initial and recurrent stroke produces central nervous system (CNS) damage, involving neuroinflammation. Receptor-mediated S1P signaling can influence neuroinflammation and has been implicated in cerebral ischemia through effects on the immune system. However, S1P-mediated events also occur within the brain itself where its roles during stroke have been less well studied. Here we investigated the involvement of S1P signaling in initial and recurrent stroke by using a transient middle cerebral artery occlusion/reperfusion (M/R) model combined with analyses of S1P signaling. Gene expression for S1P receptors and involved enzymes was altered during M/R, supporting changes in S1P signaling. Direct S1P microinjection into the normal CNS induced neuroglial activation, implicating S1P-initiated neuroinflammatory responses that resembled CNS changes seen during initial M/R challenge. Moreover, S1P microinjection combined with M/R potentiated brain damage, approximating a model for recurrent stroke dependent on S1P and suggesting that reduction in S1P signaling could ameliorate stroke damage. Delivery of FTY720 that removes S1P signaling with chronic exposure reduced damage in both initial and S1P-potentiated M/R-challenged brain, while reducing stroke markers like TNF-α. These results implicate direct S1P CNS signaling in the etiology of initial and recurrent stroke that can be therapeutically accessed by S1P modulators acting within the brain.